2016
DOI: 10.1631/jzus.b1500232
|View full text |Cite
|
Sign up to set email alerts
|

Detection of biological thiols based on a colorimetric method

Abstract: Abstract:Biological thiols (biothiols), an important kind of functional biomolecules, such as cysteine (Cys) and glutathione (GSH), play vital roles in maintaining the stability of the intracellular environment. In past decades, studies have demonstrated that metabolic disorder of biothiols is related to many serious disease processes and will lead to extreme damage in human and numerous animals. We carried out a series of experiments to detect biothiols in biosamples, including bovine plasma and cell lysates … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 21 publications
1
6
0
Order By: Relevance
“…Molecular-Dimension-Mediated Ultrasensitive and Fast-Responsive Fluorosensing of Biothiols. Given amino acids are considered as potential biomarkers and include immense biological relevance, 22,54 we perused their fluorosensing studies counting on noteworthy optical emission and N-functionality-engineered optimum-sized pores in this MOF. Fluorescence titrations were executed via sequential addition of 1 mM aqueous solution of different amino acids, having assorted functional groups, to 18a (Figures S20−S26).…”
Section: ■ Results and Discussionsupporting
confidence: 60%
“…Molecular-Dimension-Mediated Ultrasensitive and Fast-Responsive Fluorosensing of Biothiols. Given amino acids are considered as potential biomarkers and include immense biological relevance, 22,54 we perused their fluorosensing studies counting on noteworthy optical emission and N-functionality-engineered optimum-sized pores in this MOF. Fluorescence titrations were executed via sequential addition of 1 mM aqueous solution of different amino acids, having assorted functional groups, to 18a (Figures S20−S26).…”
Section: ■ Results and Discussionsupporting
confidence: 60%
“…In the presence of biothiols, the Ag-S bond is preferred; thus, the DNA binding protection of AgNPs is cancelled and the salt-induced aggregation is possible, which results in the color change from yellow to brown. Indirect colorimetric method was presented in the work of Xu et al [113]. The determination is based on 3,3′,5,5′tetramethylbenzidine (TMB) causing a reduction of Ag + , which results in a formation of AgNPs and a blue color of the solution.…”
Section: Colorimetrymentioning
confidence: 99%
“…High level of biothiols can cause serious diseases such as cardiovascular diseases, Alzheimer and Parkinson, while low level of biothiols can cause liver damage, slowed growth and weight loss. They found that the presence of biothiols can change the color of test solution from blue to colorless [6]. Muhammad Zahir et al have proved that color change of tropical fruits can be related to its intrinsic properties such as soluble solid content and pH.…”
Section: 𝐴 = ∈ 𝑙𝑐 (1)mentioning
confidence: 99%